2015
DOI: 10.1016/j.neuro.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Importance of genetics in fetal alcohol effects: Null mutation of the nNOS gene worsens alcohol-induced cerebellar neuronal losses and behavioral deficits

Abstract: The cerebellum is a major target of alcohol-induced damage in the developing brain. However, the cerebella of some children are much more seriously affected than others by prenatal alcohol exposure. As a consequence of in utero alcohol exposure, some children have substantial reductions in cerebellar volume and corresponding neurodevelopmental problems, including microencephaly, ataxia, and balance deficits, while other children who were exposed to similar alcohol quantities are spared. One factor that likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 81 publications
0
32
0
Order By: Relevance
“…Studies have shown that carbon tetrachloride induces oxidative stress in organisms and produce a large number of free radicals. Mn‐SOD and Cu/Zn‐SOD inhibit free radicals and prevent liver injury (Sipes, Sisi, Sim, Mobley, & Earnest, ; Bonthius, Winters, Karacay, Bousquet, & Bonthius, ). CAT is an antioxidant enzyme that inhibits oxidative stress by clearing the body of hydrogen peroxide, slowing the oxidation caused by carbon tetrachloride, and thus inhibiting liver injury (Lee, Hyun, Jenner, & Halliwell, ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that carbon tetrachloride induces oxidative stress in organisms and produce a large number of free radicals. Mn‐SOD and Cu/Zn‐SOD inhibit free radicals and prevent liver injury (Sipes, Sisi, Sim, Mobley, & Earnest, ; Bonthius, Winters, Karacay, Bousquet, & Bonthius, ). CAT is an antioxidant enzyme that inhibits oxidative stress by clearing the body of hydrogen peroxide, slowing the oxidation caused by carbon tetrachloride, and thus inhibiting liver injury (Lee, Hyun, Jenner, & Halliwell, ).…”
Section: Resultsmentioning
confidence: 99%
“…A decline in spleen weight indicates the occurrence of atrophy in the organ, which can reduce the immune function of the animal. Therefore, the organ indices of a mouse can directly reflect structural changes and functions of the organs and are important reference values for evaluating whether construction of a mouse model of aging is successful (Bonthius et al, 2015). The results of this study also show that oxidative aging causes a decrease in the organ indices in mice and that LP-KSFY02 could effectively alleviate the decreases in the organ indices caused by d-galactose and allow the organ indices of oxidative aging mice to remain close to those of normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate the antioxidant mechanism, this study has examined the changes in mRNA expression levels of eNOS, nNOS, nNOS and eNOS are basal-expressing tissue-constituting enzymes that participate in the entire process of learning and memory impairment (Bonthius et al, 2015). The content of nNOS and eNOS decreases after oxidative damage in the body, while increasing the levels of nNOS and eNOS in the body will also effectively control aging (Bonthius et al, 2015). In this study, L. plantarum KSFY06 can also effectively control the expression of iNOS in mouse liver tissue and spleen tissue, while increasing the expression of nNOS and eNOS to slow down the aging.…”
Section: Discussionmentioning
confidence: 99%